Literature Review: Dampak Air Yang Mengalir Dalam Proses Relaksasi - Nugraha, Siti Delvia; Keledar, Sri Hartuti Irawanto; Syakinah, Icha Marwah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Water is an essential element for life. Without water no living thing would survive on the face of the earth. Even 70% of the earth is filled with water. Then what does water have to do with the relaxation process does just listening to flowing water make our body relax? According to Charles W Moremen the element of water visually possesses familiar, simple characteristics, and possesses infinite appeal. The World Health Organization (WHO) states that 29% of adults worldwide have experienced general mental stress, including among them is depression. The presence of rapid urbanization, it is estimated that by 2050, about 68% of the world’s population will live in urban areas, the impact of which is an increase in people experiencing mental stress. Water views or waterscapes can be a solution in dealing with the issue.